1989
DOI: 10.1007/bf00964814
|View full text |Cite
|
Sign up to set email alerts
|

Monoamines and metabolites in autopsied brain tissue from cirrhotic patients with hepatic encephalopathy

Abstract: Alterations in the metabolism of monoamine neurotransmitters have been proposed to be involved in the development of the hepatic encephalopathy (HE) associated with experimental and human liver failure. In order to evaluate this hypothesis, the monoamines and some of their metabolites were measured in homogenates of caudate nucleus (CAU), prefrontal (PFCo) and frontal cortex (FCo) dissected from brains obtained at autopsy from nine cirrhotic patients who had died in hepatic coma and an equal number of control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 39 publications
4
37
0
1
Order By: Relevance
“…In HE patients, dysfunction of the liver results in disturbances of amino acid metabolisms and subsequent elevation of plasma and brain contents of aromatic amino acids such as Trp and Tyr (Bergeron et al, 1989). The elevation of these aromatic amino acids leads to increased synthesis of 5HT, DA, and NA in the brain (Cascino et al, 1982;Bernardini and Fischer, 1982;Fanelli et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In HE patients, dysfunction of the liver results in disturbances of amino acid metabolisms and subsequent elevation of plasma and brain contents of aromatic amino acids such as Trp and Tyr (Bergeron et al, 1989). The elevation of these aromatic amino acids leads to increased synthesis of 5HT, DA, and NA in the brain (Cascino et al, 1982;Bernardini and Fischer, 1982;Fanelli et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It would, however, be unwise to extrapolate this to the situation in man, given that some subjects experience 'late' withdrawal and clinically some behavioural disorders secondary to alcohol dependence, which may have biochemical correlates; for example depression can take up to 4 weeks after withdrawal to resolve. There is also the possibility that pathological changes associated with long-term alcohol dependence, for example liver cirrhosis, may exert permanent effects on Trp disposition (for example, see Rössle et al 1986;Bergeron et al 1989). Accordingly, the Trp metabolic status of human alcoholism should best be studied in long-term abstinence and in subjects not afflicted with overt organ damage, or, preferably, in offspring of adults with a family history of alcoholism before their exposure to alcohol.…”
Section: The Tryptophan Metabolic Status In Human Alcoholismmentioning
confidence: 99%
“…This increase in MAO-A gene expression was found to be associated with increased activities of the enzyme and increased densities of catalytic sites on the enzyme protein (Mousseau et al, 1997). Moreover, studies of the same brain extracts revealed increased concentrations of homovanillic andhydroxyindoleacetic acids, the final metabolites of dopamine and serotonin, respectively (Bergeron et al, 1989). Increased concentrations of 5-hydroxyindoleacetic acid were also reported in cerebrospinal fluid from patients (Young & Lai, 1980) and experimental animals (Bergeron et al, 1995) with chronic liver failure.…”
Section: Portal-systemic Encephalopathy (Pse)mentioning
confidence: 89%
“…Studies in autopsied brain tissue from cirrhotic patients (Bergeron et al, 1989) and from rats with PCS (Bergeron et al, 1995) reveal several-fold increases in concentration of the dopamine metabolite homovanillic acid, a finding that could result from increased activities of monoamine oxidase reported in the same material (Mousseau et al, 1997). In another study, densities of the postsynaptic dopamine D 2 receptor were significantly reduced in pallidum/putamen from cirrhotic patients (Mousseau et al, 1993) a finding that could have resulted from manganese deposition in the brains of these patients .…”
Section: Portal-systemic Encephalopathy (Pse)mentioning
confidence: 92%